2017
DOI: 10.1080/21691401.2017.1392314
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic acid derivatized hydroxylated fullerenes as drug delivery vehicles for docetaxel: an explorative study

Abstract: The objective of the present study was to deliver docetaxel to cancerous cells with enhanced efficacy and safety profile, using aspartic acid linked fullerenols. This aspartic acid derivatized fullerenol conjugate linked with docetaxel was characterized by UV, FT-IR and NMR spectroscopy. Studies for particle size, PDI, zeta potential and FE-SEM were also performed. The conjugate was evaluated for release kinetics, cancer cell cytotoxicity, cellular uptake using confocal laser microscopy and also for pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Some studies have shown that encapsulation or micro-encapsulation of fullerene in special carriers such as cyclodextrins and chemical functionalization by amino acid, carboxylic acid, poly hydroxyl group, and amphiphilic polymers can enhance the hydrophilicity and drastically reduce fullerene’s toxicity. The biological efficacy of water-soluble fullerenes has been investigated in vitro, indicating its low toxicity [27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that encapsulation or micro-encapsulation of fullerene in special carriers such as cyclodextrins and chemical functionalization by amino acid, carboxylic acid, poly hydroxyl group, and amphiphilic polymers can enhance the hydrophilicity and drastically reduce fullerene’s toxicity. The biological efficacy of water-soluble fullerenes has been investigated in vitro, indicating its low toxicity [27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Docetaxel (DTX) was delivered to human breast cancer cells (MDA-MB-231 cell line) with enhanced efficacy and safety using aspartic acid linked fullerenols. Cytotoxic investigations proved that conjugated NDDP has ~4.3-fold lower IC 50 with significant cellular uptake and high bioavailability of drug (~5.8-fold higher as compared to free DTX) and nano-constructs were also immuno-compatible [63]. DTX has also been delivered in another in vitro cancer model using carboxylated and acylated C 60 -fullerenes as carrier vehicles to MCF-7 and MDA-MB231 cancerous cells.…”
Section: Inorganic Nddps Implicated In Anti-cancer Therapymentioning
confidence: 99%
“…According to properties of nanomaterials, nano‐drug carriers can be divided into inorganic nanocarriers (such as graphene [5], carbon nanotubes [6], fullerenes [7] and oxide nanoparticles [8–10]), organic nanocarriers (such as liposomes [11], polylactic acid [12], chitosan [13]) and metal nanocarriers including Au nanoparticles [14], Pd nanosheets [15], Pd@Au nanoparticles [16] etc.). In the field of nano drugs, researchers are paying more attention to control the design and construction of nanoparticles with special morphology and topology to better use for drug delivery.…”
Section: Introductionmentioning
confidence: 99%